Legalitas Perkawinan Di Luar Islam (Nikah Al-kuffar) Menurut Ibnu Taimiyah - Samsul Hadi (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
Marriage is an institution that exist in every society and religion. Every society and religion have a procedure for each different from each other. Whether the marriages were valid under Islamic law. Islam is a religion that recognizes the plurality of society and religion as a reality of life. Ibn Taimiyya had an opinion about the validity of marriages outside of Islam (al-kuff?r marriage/nik?h al-kuff?r). Ibnu Taimiyya opinion was based on AlQur'an and as-Sunnah (traditions) and the opinions of some friends (sahabat). Ibn Taimiyya opinion was consistent with the principles of tolerance in Islam; religious freedom, mutual respect, and justice. Ibn Taimiyya opinion is very important in creating a harmonious relationship between religious.